Characteristics of multiscale vortices in the simulated formation of Typhoon Durian (2001). (3rd August 2016) - Wang, Yaping; Cui, Xiaopeng; Huang, Yongjie
Abstract: The formation of Typhoon Durian (2001) was simulated well by the Weather Research and Forecasting model. The vorticity field was separated into three scales: small scale ( L < 30 km), intermediate scale (30 km < L < 120 km), and system scale ( L > 120 km), where L is wavelength. During the formation, small‐scale vorticity anomalies, associated with convection, aggregated radially inward and rotated anticlockwise. The system‐scale vorticity field presented a distinct mid‐level vortex before genesis, and then a well‐organized low‐level vortex. The spectral power of the low‐level vorticity at the small scale barely changed, while that at the system scale continued to grow steadily. The vorticity growth or spin‐up of the near‐surface tropical cyclone embryo was mainly due to the convergence of vertical vorticity flux at the planetary boundary layer. The positive (negative) effect of vorticity flux convergence at lower (middle‐to‐upper) levels appears to cause the shift of system‐scale vorticity center from the middle to lower troposphere.